A Modified Hierarchical Attribute-Based Encryption Access Control Method for Mobile Cloud Computing (International Journal of Food and Nutritional Sciences, 2021)
Cloud computing is an Internet-based computing pattern through which shared resources are provided to devices on demand. It is an emerging but promising paradigm to integrating mobile devices into cloud computing, and the integration performs in the cloud based hierarchical multi-user data-shared environment. With integrating into cloud computing, security issues such as data confidentiality and user authority may arise in the mobile cloud computing system, and it is concerned as the main constraints to the developments of mobile cloud computing. In order to provide safe and secure operation, a hierarchical access control method using modified hierarchical attribute-based encryption (M-HABE) and a modified three-layer structure is proposed.